ACTUAL PROBLEMS OF ASSESSING THE PROPERTY COMPLEX OF THE ORGANIZATION - A. Pepoyan (Вестник университета)
The urgency of the topic is determined; the content of the basic concepts is disclosed in accordance with the current legislation of the Russian Federation. The historical aspects of forming appraisal practice in connection with the development of market processes are pointed out, the main theoretical basis of valuation activity is reflected. Regulation system interaction between banks, creditors and appraisers are considered. The existing shortcomings in the methodology used today to assess real estate are discussed. The options for their systematization and adaptation to the current market conditions are examined.